Contrast-induced generalized bullous fixed drug eruption resembling Stevens-Johnson syndrome. Issue 4 (2nd October 2019) - Gavin, Meredith; Sharp, Leigha; Walker, Kendra; Behrens, Emily; Akin, Russell; Stetson, Cloyce L.
Abstract: A 59-year-old woman with end-stage renal disease presented for suspected Stevens-Johnson syndrome that was ultimately diagnosed as generalized bullous fixed drug eruption (GBFDE) secondary to the administration of iodinated nonpolar radiocontrast. The patient had three previous episodes of a generalized bullous eruption after a thrombectomy, fistulogram, and an arteriovenous fistula revision, all requiring radiocontrast administration. Biopsies taken after previous eruptions demonstrated full-thickness epidermal necrosis, and she was diagnosed with Stevens-Johnson syndrome thought to be due to allopurinol. However, against medical advice she continued taking allopurinol and remained asymptomatic until the current presentation. Based on the clinical appearance and time frame of the eruptions, the patient was diagnosed with GBFDE due to radiocontrast. GBFDE, a rare variant of a fixed drug eruption, can be misdiagnosed as Stevens-Johnson syndrome due to their overlapping features of drug-induced whole-body blisters and variable degrees of epidermal necrosis.